Reading curriculum-based measurement: screening Portuguese students at risk for dyslexia - Vaz, Paula Marisa Fortunato (2016)
This poster presentation will present results from a study developed within the rst level of support, primary prevention, which was focused on identifying and preventing academic problems from occurring in those students enrolled in a school setting. How progress measurement was used in reading comprehension as a universal school screening system for third-grade Portuguese students will be analyzed. Results for level and growth in both groups of students at risk and not at risk and the risk factors presented in the study participants will also be presented and discussed.